PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BEDAK PADAT PRODUK INEZ KOSMETIK - Dania Ayu Rahmawati, 14.05.51.0003; Prabowo, Rokh Eddy (Students' Journal of Economic and Management, 2018)
The aim of this research is to find out the effect of each independent variable: the product quity, brand image, price perception and promotion toward decision making in the process of purchasing Ines cosmetic powdery product. The population of this research was the buyer of Inez cosmetic powdery product, meanwhile 100 people was taken as the sample. The primary data was processed using SPSS 19. The result showed that all the indicators were valid and all the variable were reliable. Each of the variable positively and significantly influenced to the customer’s decision making in the process of purchasing Ines cosmetic powdery product. Those four variables influence 85,3 percent of the customer’s decision making in the process of purchasing Inez cosmetic powdery product. Another variable which influences the customer’s decision making is product design, product, brand loyality, and location. Keywords: product quaity, brand image, price perception, promotion, and customer’s decision making